Impact of the COVID-19 pandemic on racial and ethnic discrimination - a systematic review - Kozioł, Ilona Zofia; Budzyńska, Julia; Leśniewska, Magdalena; Kopystecka, Agnieszka; Patryn, Rafał (Journal of Education, Health and Sport, 2023)
The COVID-19 pandemic has affected the entire society, being particularly detrimental to ethnic and racial minorities. Moreover, the problems faced by these communities are characterised and the measures that can be implemented to improve their situation are put forward. Many authors have suggested introducing the solutions according to the socio-ecological model which considers individual, organisational, community and policy factors. Due to the lack of trust of ethnic minorities in health care, no effort should be spared to restore their trust. To achieve this goal, educational programs should be carried out to dispel doubts about research and treatment. Furthermore, the impact of social media on the dissemination of discriminatory content should be meticulously analysed. The present paper is a systematic review of current literature, which analyses the authors` opinions on racial and ethnic discrimination during the COVID-19 pandemic.